Ecological direction in the system of knowledge on population - S. D. Valentey; N. G. Dzhanaeva (Статистика и экономика, 2017)
Vladimir Putin, the President of the Russian Federation, signed the decree on January 5, 2016, declaring Ecology Year to be held in 2017 in Russia. This decree aims at drawing attention to the significance of environmental problems, and improving the situation with environmental security in the country. Our article considers the development of scientific research exploring the interrelations and interdependencies between population and environment, theoretical approaches and methodology of these studies. On the scientific and practical side the article analyses the available typologies of demoecological situations and develops own demoecological typology as a policy instrument aimed at sustainability in population development and environmental security.In the 70s – 90s of the last century, the scientific community paid close attention to the “environmental issue” problem, and there existed the awareness of the interdependence between environment and population. The study on population-environment interdependence was conducted in the Center for Population Studies at the Faculty of Economics of Lomonosov Moscow State University within the framework of new field of the system of population knowledge – ecology of population, considering the demographic and environmental development in close connection. Multiple demoecological situations identified in the studies, were logically followed by the development of the typology of demoecological systems using environmental principles (stage development, diversity and territorial differentiation). The unification of all economic regions of the Soviet Union according to various demoecological factors allowed the authors to summarize all diverse situations, showing similarities in their development, and to highlight the types of interactions between the elements of demoecological regional systems that can be considered to be the basis of comprehensive long-term program of population development. In the late 90-s, this approach, using ranking and indexing methodology was applied to assess the level of demoecological development of the Russian Federation regions. It was resulted in the creation of the specified and amended (in relation to the study conducted in the beginning of 1980s) system of basic indexes in order to monitor changes in demoecological systems, and new, integrated indexes, more accurately characterizing the state of the environment and population development.The research, made in this period, has led to resulting conclusion about the scientific and practical feasibility to take into consideration the typological features of the region while developing long-term programs for sustainable socio-economic development. The similarity of the same demoecological situations allows using the experience of the regions belonging to the same type, reducing the risk of errors in setting the objectives of development programs and the development of measures for their implementation. This conclusion, made 25 years ago, is very relevant today, when a growing number of experts argues that replication of methods of implementation of regional policy is common thing for all the regions of the Russian Federation and has a negative impact on the unity of economic space of the country.